Preliminary results of in vitro fertilization for the endangered murciano-levantina bovine breed (2004)
ASBTRACT: The Murciano-levantina cattle from the Spanish South-East belongs to a bovine endangered breed under the special protection of FAO (WWL-DAD:3)*. Their characteristics of rusticity, longe- vity, docility and disease resistance make interesting the recovery of the breed. The objective of the present work was to deter mine the efficiency of in vitro bovine embryo production using oocytes collected from post mortem ovaries fertilized with frozen thaw sperm obtained either from commercial or Murciano-levantina bulls. Cumulus oocyte complexes were matured for 24 h in TCM199 with 10% FBS, 2mM L-glutamine, 0.2 mM sodium pyruvate, 0.3 µg/mL LH and µg/mL FSH. Oocytes presumed matured were fertilized with Percoll-prepared sper m (750.000/mL) in IVF-TALP as described by Parrish et al. (Biol. Reprod 38:1171-1180, 1988). Zygotes (at 18 h) or two-cell stage embryos (at 48 h) were assessed by staining with Hoechst 33342 (µg/mL; 20 min) under an epifluorescence microscopy. The experiment was replicated on 4 occasions.The results of penetration (PEN-%), average number of spermato- zoa inside the oocyte (S/O), monos permy (MON- %) putative embryos (zygotes with two pronuclei, 2 PN-%) and percentages of cleavage at 48 hours (Table 1) were recorded. The results show that early embryos can be obtained with no difference with the source of sperm used in the monospermy and the cleavage rate between commercial and Mur- ciano-levantina sperm (p>0.05). *Lista Mundial de Vigilancia para la Diversidad de los Animales Do- mésticos (1997). http:// www.fao.org/docrep/V8300S/ V8300S00.htm